The Effect of Feeding Time Restriction During the Starter Period on Compensatory Growth and Thyroid Hormone Concentrations of Broiler Chickens - Azis , A.; Zubaidah; Berliana (International Journal of Poultry Science, 2013)
The objective of the study was to evaluate the effect of feeding time restriction during starter period on compensatory growth and thyroid hormone concentration of broiler chickens. Four hundred of 7 days-old unsexed broiler chicken of Ross commercial strain were used a completely randomized design with 4 treatments. The treatments were: broilers were fed ad libitum as control group (P-0); broilers had to feed during 15 h/d (07:00 to 10:00; 12:00 to 15:00; 17:00 to 20:00; 22:00 to 01;00; 03:00 to 06:00) from 7-21 d of age (P-1); broilers had free access to feed during 12 h/d (07:00 to 10:00; 13:00 to 16:00; 19:00 to 22:00; 01:00 to 04:00) from 7-21 d of age (P-2); broilers had free access to feed during 9 h/d (07:00 to 10:00; 15:00 to 18:00; 23:00 to 02:00) from 7-21 d of age (P-3). The treatments consisted of 5 replicates with 20 chicks per pen. Feed intake and body weight gain of feeding time restriction broiler (P-3, P-2 and P-1) was significantly lower than broiler fed ad libitum (P-0) during 7 to 21 d of age. During this period, feed conversion ratio of P-3 had better than P-0, P-1 and P-2. There were no significant difference among all treatments on feed intake, body weight gain and feed conversion ratio during realimentation period. There were significantly lower T3 and T4 of all feeding time restriction broiler than broiler fed ad libitum. However, T3 and T4 were normalized during realimentation period. It was concluded that feeding time restriction during starter period had compensatory growth phenomenon and similar body weight with control and thyroid hormones profile were normalized during realimentation period.